Halifax gathering of the Future of First Nations, Inuit and Métis Broadcasting: Conversation & Convergence series - Baby, Aggie; Beaton, Brian; Bonin-Labelle, Geneviève; Clair, Annie; Fiallos, Francella; Gagnon, John; Googoo, Maureen; King, Carolyn; King, Gretchen; Marshall, George; Martin, Catherine Anne; Metawabin, Mike; et al. (Université d'Ottawa | University of Ottawa, 2017)
A collection of documents, audio recordings, and programming resulting from the fifth gathering of the Future of First Nations, Inuit and Métis Broadcasting: Conversation & Convergence series held in Halifax, Nova Scotia, on May 18th, 2017.
Keywords: First Nations; Inuit; Métis; Broadcasting; Policy; CRTC; Radio; Halifax